Hypertriglyceridemia: An Infrequent, Difficult-to-predict, Severe Metabolic and Vascular Problem Associated with Estrogen Administration - Whayne, Thomas F. (Current Vascular Pharmacology, 2020)
Supplementary estrogen plays important roles for female patients as convenient birth control, relief of postmenopausal symptoms, and in the management of other selected problems. However, as is the case for essentially all medications, there are side effects. Short of a major pulmonary embolus, the most severe side effect of estrogen would appear to be sporadic, rare, and severe hypertriglyceridemia associated with acute pancreatitis. The occurrence of this fortunately rare problem usually happens in the presence of some preexisting and usually mild increase in triglycerides (TG). A case of chronic and severe recurrent acute pancreatitis is described in the introduction and the management was complete estrogen avoidance. Started close to menopause and continued for a relatively short period, estrogens may have some cardiovascular (CV) benefit but the general recommendation is not to prescribe them for CV disease prevention. Estrogens may contribute to decreased diabetes mellitus (DM) risk and control. Administration of estrogens by the transdermal route may decrease some problems such as venous thromboembolism (VTE) and elevation of TG. Administration of estrogen in the right situation brings significant benefit to the female patient but skillful, careful, and knowledgeable use is essential.
Keywords: triglycerides